The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1155/2022/4804408
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Role of Pumpkin Parts as Pharma-Foods: Antihyperglycemic and Antihyperlipidemic Activities of Pumpkin Peel, Flesh, and Seed Powders, in Alloxan-Induced Diabetic Rats

Abstract: Pumpkin is a well-known vegetable, among the members of Cucurbitaceae family, due to its importance as pharma food. Keeping in view the antidiabetic and plasma lipids lowering potential of pumpkin, the present study was conducted to investigate that, which part of pumpkin (peel, flesh, and seeds), possess more bioactive compounds, exhibiting antihyperglycemic and antihyperlipidemic potential. Albino rats with 190-210 g body weight were divided into 11 groups. Five rats were included in each group; group A was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…The significance of maintaining a healthy diet in the fight against infectious diseases cannot be overstated. Pumpkin, its flesh, peel, and seed powders are abundant in crude fiber and proteins, particularly pumpkin seed proteins containing peptides vital in promoting healthy human body functions . A study conducted by Quanhong et al revealed that the hypoglycaemic effects of pumpkin are attributed to polysaccharides extracted from the pumpkin fruits.…”
Section: Clinical Trials (Human and Animal Studies)mentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of maintaining a healthy diet in the fight against infectious diseases cannot be overstated. Pumpkin, its flesh, peel, and seed powders are abundant in crude fiber and proteins, particularly pumpkin seed proteins containing peptides vital in promoting healthy human body functions . A study conducted by Quanhong et al revealed that the hypoglycaemic effects of pumpkin are attributed to polysaccharides extracted from the pumpkin fruits.…”
Section: Clinical Trials (Human and Animal Studies)mentioning
confidence: 99%
“…Pumpkin, its flesh, peel, and seed powders are abundant in crude fiber and proteins, particularly pumpkin seed proteins containing peptides vital in promoting healthy human body functions. 94 A study conducted by Quanhong et al 95 revealed that the hypoglycaemic effects of pumpkin are attributed to polysaccharides extracted from the pumpkin fruits. The study evaluated the hypoglycemic activity of these polysaccharides on alloxan-mediated diabetic rats, where improved levels of blood insulin and decreased blood glucose levels were observed, indicating better glucose tolerance.…”
Section: Clinical Trials (Human and Animal Studies)mentioning
confidence: 99%
“…Resultantly it can be concluded that pre-treatments before drying of pumpkin could be the effective processing techniques to obtain good quality pumpkin products with enhanced nutritional parameters ( Chao et al, 2022 ). Pumpkin peel, flesh and seeds powders contain good quality protein and oils, containing essential amino acids and fatty acids ( Hussain et al, 2022 ).…”
Section: Pumpkin Powders; Concentrated Sources Of Nutrients and Phyto...mentioning
confidence: 99%
“…Food combinatio ns containing immunity boosting nutrients are needed to be explored and marketed in current post COVID 19 period, which can play vital role against common viruses and novel corona virus improving the immunity all around the world [1]. Nutrition, a key factor affecting humans health, must be the key strategy to encounter the attack of COVID 19. That is why the populations with poor diet and bad eating habits have greater chances to be affected by viral diseases, especially the novel coronavirus.…”
Section: Introductionmentioning
confidence: 99%
“…Relation of COVID 19 pandemic is very closely related to body immunity and in current situation, protection of body from viral diseases can only be done with the use of immunity booster diets. Pumpkin has been included prominently in the selection of vegetables to be preferred during and after COVID 19…”
Section: Introductionmentioning
confidence: 99%